Absence of CHRDL1 and FOXC1 sequence changes in two brothers with Megalocornea-Mental Retardation Syndrome - Gebril OH; Cheong SS; Hardcastle AJ; Abdelraouf ER; Eid SR; Elsaied M (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Megalocornea is a defining feature of megalocornea-mental retardation (MMR) syndromealso called Neuhäuser syndrome, a rare condition of unknown etiology. Here we describe a family with two sons, who were diagnosed with megalocornea, mild mental subnormality and microcephaly, in addition to limb anomalies in the form of clinodactyly in the younger brother, while extradigit and clinodactyly was seen in the older brother. Parents are second degree cousins with no obvious family history of similar problems.Mutations in CHRDL1 are known to cause X-linked megalocornea (MGC1) and FOXC1 mutations cause a wide range of syndromic or non-syndromic anterior segment dysgeneses (ASD) phenotypes. Sanger sequencing of CHRDL1 and FOXC1 did not identify any potential disease causing variants in this family. Conclusions: Megalocornea-mental retardation (MMR) syndrome isa genetically and phenotypically heterogeneous condition. In this Egyptian family, CHRDL1 and FOXC1 have been excluded as the cause. Next generation sequencing is required to identify the genetic cause of the syndrome in this family.